Network Centric Warfare (NCW) as Defense Resilience: Strengthening National Defenses Through Integrated Air Defense Systems - Wisnu Candra Wijaya (Jurnal Impresi Indonesia, 2025)
This study discusses the importance of applying Network-Centric Warfare (NCW) to strengthen Indonesia's national air defense resilience. The primary issue identified is the low integration level of the TNI air defense system, resulting in weak air deterrence and frequent violations of Indonesian airspace by foreign aircraft. The research focuses on the national air defense system and NCW as a strategy for enhancement. Using a descriptive-analytical method, the study analyzes secondary data from official documents, defense policies, and TNI military doctrine, providing a comprehensive overview of the current air defense status and how NCW can enhance military operations. Findings reveal that NCW significantly improves situational awareness by enabling real-time information exchange among military components such as radars, sensors, and air weapons systems. It facilitates better unit coordination and faster battlefield decision-making. However, challenges remain due to reliance on diverse foreign military equipment with different communication standards, cybersecurity vulnerabilities, and limited human resources proficient in military communication technology. In conclusion, while NCW holds great potential to improve Indonesia’s air defense resilience, its optimal implementation requires modernizing communication infrastructure, enhancing interoperability among military systems, and developing skilled human resources. With strategic coordination, NCW can become a robust backbone of air defense, effectively countering modern threats like stealth fighters, hypersonic missiles, and armed drones.